2013
DOI: 10.1016/j.ejca.2012.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Descriptive epidemiology of sarcomas in Europe: Report from the RARECARE project

Abstract: We now differentiate between the requirements for new and revised submissions. You may choose to submit your manuscript as a single Word or PDF file to be used in the refereeing process. Only when your paper is at the revision stage, will you be requested to put your paper in to a 'correct format' for acceptance and provide the items required for the publication of your article. To find out more, please visit the Preparation section below. Highlights Highlights are mandatory for this journal for all article ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

32
454
2
13

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 559 publications
(501 citation statements)
references
References 31 publications
32
454
2
13
Order By: Relevance
“…Relative survival was very low in genitourinary tumors of females including uterus and highest in the STS of skin, similar to published reports 4, 15. The population based study from Europe reported lowest survival rates in STS of heart and mediastinum followed by uterine STS 4.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Relative survival was very low in genitourinary tumors of females including uterus and highest in the STS of skin, similar to published reports 4, 15. The population based study from Europe reported lowest survival rates in STS of heart and mediastinum followed by uterine STS 4.…”
Section: Discussionsupporting
confidence: 90%
“…Common tumor sites in different age groups were also similar to other population‐based studies 2, 4.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations